25 Care after Resuscitation: An Innovative Early Psychological Support Service Proven to Improve the Quality of Life, Cognitive Function, and Ability to Return to Work – An Early Intervention for Cardiac Arrest Survivors and their Caregivers. (6th June 2015) - Islam, Shahed; Keeble, Thomas; Davies, John; Magee, Neil; Balasubramanian, Rajesh; Watson, Noel
Abstract : Introduction: In the UK, an estimated 30, 000 out of hospital cardiac arrests (CA) are treated by emergency medical services annually. Better access to early chain of survival is expected to result in improved survival rates. Therefore, more patients are expected to live with the consequence of the CA, which can range from impairment of cognitive function, deterioration in emotional well-being and perceived quality of life (QoL). Follow-up of patients at the Essex Cardiothoracic Centre, in a current research trial involving CA survivors, emphasised that standard psychological support arrangements for these patients and their caregivers are alarmingly inadequate. Last year in the Netherlands, a randomised trial demonstrated that introduction of early psychological support service significantly improved QoL for survivors of CA compared with control group, paving the way for this to be incorporated in routine clinical practice. This study also showed that a higher percentage of patients (50%) receiving the intervention returned to work 3 months after CA compared to 21% in the control group. Methods and results: In the setting of the CARE after resuscitation trial, we are the first NHS trust investigating the effects of a comprehensive psychological support service in patients following CA. In group 1, 20 patients and their caregivers have been recruited at least 3 months after the CA, to assess the effectiveness of current 'standard care'. About 50% of these patients still experienced moderate to severe depression, 20% suffered from post-traumatic stress disorder and they were referred to a clinical psychiatrist for further management. In group 2, a further 20 patients, after surviving a CA with good neurological recovery and their caregivers are reviewed on the ward prior to discharge by a senior ICU nurse and a cardiologist. They are given a leaflet detailing life after cardiac arrest and the support network in place, and given a novel telephone help line (managed by ICU nurses that they can call during working hours). Once discharged patients are contacted by the ICU nurse within 48 h to ask about their well-being. Patients and caregivers are then invited back to a dedicated cardiac arrest outpatient clinic after 6–8 weeks, where they are seen by a multi-disciplinary team including cardiologist, ICU nurse and psychiatrist. Patients and their caregivers will then be reviewed in 6 months to re-evaluate their QoL and their ability to return to work. Conclusion: We hope that the observations from the Netherlands can be replicated here in the "intervention group" and these data will be presented at the BCS conference in June 2015. If successful, we will disseminate our experience with the rest of the UK so that, all survivors of CA and their caregivers can benefit from this service.